Konsep dan Perlindungan Hukum atas Tindakan Administrasi Pemerintahan Berupa Tidak Melakukan Perbuatan Konkret (Omission) - Asimah, Dewi; Erliyana, Anna (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
After the enactment of Law No. 30 of 2014 on Government Administration (Government Administration Law or abbreviated as UU AP in Indonesian) and Supreme Court Regulation (Perma) No. 2 of 2019, the authority of the Administrative Judiciary has expanded. The Administrative Judiciary adjudicates disputes related to administrative decisions and handles disputes related to government administrative actions (Factual Conduct). Actions that can be sued include active (performing concrete/Factual Conduct - commission) and passive (not performing concrete/Factual Conduct-omission) actions. Although Government Administration Law and Supreme Court Regulation do not provide detailed explanations regarding the meaning and criteria of passive government actions, based on studies, several criteria can be used to assess whether passive government actions can be considered unlawful. These criteria include the existence of a legal obligation that must be performed by an administrative official. The action is within the scope of their authority, the official intentionally does not fulfill the obligation, the action violates legislation and legal obligations, or the plaintiff’s subjective rights, and the existence of a permissible claim for actual damages. In terms of legal protection, citizens can file a lawsuit in the Administrative Court against the failure of a government body or official to perform a concrete action. However, in practice, various problems still arise, such as the time limit for filing lawsuits, the obligation to pursue administrative remedies first, and issues related to the tacit authorization concept.